Improving cardiovascular magnetic resonance access in low- and middle-income countries for cardiomyopathy assessment: rapid cardiovascular magnetic resonance. (10th February 2022) - Menacho, Katia Devorha; Ramirez, Sara; Perez, Aylen; Dragonetti, Laura; Perez de Arenaza, Diego; Katekaru, Diana; Illatopa, Violeta; Munive, Sara; Rodriguez, Bertha; Shimabukuro, Ana; Cupe, Kelly; Bansal, Rajiv; et al.
Abstract: Aims: To evaluate the impact of a simplified, rapid cardiovascular magnetic resonance (CMR) protocol embedded in care and supported by a partner education programme on the management of cardiomyopathy (CMP) in low- and middle-income countries (LMICs). Methods and results: Rapid CMR focused particularly on CMP was implemented in 11 centres, 7 cities, 5 countries, and 3 continents linked to training courses for local professionals. Patients were followed up for 24 months to assess impact. The rate of subsequent adoption was tracked. Five CMR conferences were delivered (920 attendees—potential referrers, radiographers, reporting cardiologists, or radiologists) and five new centres starting CMR. Six hundred and one patients were scanned. Cardiovascular magnetic resonance indications were 24% non-contrast T2* scans [myocardial iron overload (MIO)] and 72% suspected/known cardiomyopathies (including ischaemic and viability). Ninety-eighty per cent of studies were of diagnostic quality. The average scan time was 22 ± 6 min (contrast) and 12 ± 4 min (non-contrast), a potential cost/throughput reduction of between 30 and 60%. Cardiovascular magnetic resonance findings impacted management in 62%, including a new diagnosis in 22% and MIO detected in 30% of non-contrast scans. Nine centres continued using rapid CMR 2 years later (typically 1–2 days per week, 30 min slots). Conclusions: Rapid CMR of diagnostic quality can be delivered using available technology in LMICs. When embedded in care and a training programme, costs are lower, care is improved, and services can be sustained over time. Structured Graphical Abstract: Structured Graphical Abstract Rapid cardiovascular magnetic resonance (CMR) is an international partnership project that aimed to evaluate the impact of a simplified and less expensive CMR protocol embedded with an educational programme to assess a wide spectrum of cardiomyopathies in 11 centres from national/state capital in five low- and middle-income countries (LMICs) with available technology. Over a 5-year period, we delivered an education programme to 920 referrers. Six hundred and one patients were scanned, reducing the time of scanning to <22 min, potentially saving costs and impacting on patients' care. Our project highlights the potential and beneficial role of rapid CMR in LMICs. CMR, cardiovascular magnetic resonance; LMICs, low- and middle-income countries; CMP, cardiomyopathy.